2010
DOI: 10.1111/j.1749-6632.2010.05475.x
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical studies with IRX‐2 and thymosin α1 in combination therapy

Abstract: Thymosin alpha1 (Talpha1) is a 28 amino acid biologically active protein with pleiotropic immune enhancing activity. IRX-2 is a primary cell-derived biologic containing multiple cytokines that enhance dendritic cell maturation, promote T-cell growth and differentiation, and inhibit tumor-mediated apoptosis of T cells. IRX-2 is being developed as an immunotherapeutic agent as a novel T-cell adjuvant platform for vaccines as well. Based on their biological activities, thymosin alpha1 and IRX-2 were predicted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Irx3 belongs to a superfamily of transcription factors that can act as either repressors or activators of gene expression ([ 44 , 45 ] and is commonly linked with embryonic development of neuronal and cardiac tissue. Irx3 is also associated with malignancies in humans, such as particular subtypes of leukemia, where it may influence T cell maturation checkpoints [ 46 , 47 ]. While the role that irx3 plays in immunity to M .…”
Section: Discussionmentioning
confidence: 99%
“…Irx3 belongs to a superfamily of transcription factors that can act as either repressors or activators of gene expression ([ 44 , 45 ] and is commonly linked with embryonic development of neuronal and cardiac tissue. Irx3 is also associated with malignancies in humans, such as particular subtypes of leukemia, where it may influence T cell maturation checkpoints [ 46 , 47 ]. While the role that irx3 plays in immunity to M .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies by the Hadden group, with the combination of Ta1 and IRX-2, were performed in hydrocortisone-suppressed mice and the combination was shown to be superior to either agent alone [19]. Based on those studies and the observation by the Garaci group that Ta1 and IL-2 were superior to either alone, studies were undertaken to combine Ta1 with IRX-2 [20,21,23,24]. The studies suggested synergy, and as shown in Figure 1, significant decrease in tumor growth and survival can be demonstrated in the LLC model.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Although the majority of patients benefit as defined by enhanced survival due to lymphocyte infiltration, a number of patients failed to benefit. Thus, the combination of IRX-2 with another biologic such as Ta1 is an attractive hypothesis with respect to generating lymphoid cells which may be missing in those individuals who fail to respond to IRX-2 [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Tα1 is a 28-amino acid peptide hormone which was isolated from animal thymus originally, and plays vital roles in immune regulation, promoting natural killer cell activity, enhancing the anti-infection ability of the host and inhibiting the growth of cancer cells (Zavaglia et al 2000). Tα1 increase T-cell markers on immature T cells and enhance immune responses in a wide variety of animal models (Hadden 2001;Naylor and Hadden 2010). Currently, Tα1 is widely used in curing chronic hepatitis B and C and reducing adverse effects on tumors treatment from chemotherapy or radiotherapy (Billich 2002;Ciancio and Rizzetto 2010;Garaci et al 2007;Goldstein and Goldstein 2009).…”
Section: Introductionmentioning
confidence: 98%